Effect of Crack Healing of SiC according to Times of SiO2 Colloid Coating. (2nd June 2013) - Nam, Ki Woo
Abstract : Crack healing behavior of SiC ceramics with large crack width has been studied as a function of coating and heat treatment. The SiO2 colloid coating was carried out on two types: hydrostatic pressure coating and roll coating. The crack healing was one hour at 1173 K in air. The crack part formed SiO2 oxides until the critical times by a hydrostatic pressure method. The crack does not anymore heal if it exceeds the critical times. The crack part and the base part have many O components and Si components regardless of the times of coating and heat treatment. The combined hydrostatic and rolling coating method did not have nearly an effect on crack-healing for large crack width over 1.4 μ m. The study for more effective healing of a large crack width must be carried out in the future.